Effects of harman and harmine on naloxone-precipitated withdrawal syndrome in morphine-dependent rats - ARICIOĞLU, FEYZA (My University, 2003)
The effects of the beta-carbolines, harman and harmine, on naloxone-precipitated withdrawal syndrome in morphine-dependent rats were investigated. Two morphine pellets containing 75 mg morphine base were implanted subcutaneously in the scapular area of adult male Wistar rats (200-250 g) under light ether anesthesia. Rats were then assigned to several groups (n = 12 for each group). Seventy-two hours after morphine implantation, harman (5 and 10 mg/kg), harmine (5 and 10 mg/kg) or saline was injected to rats intraperitoneally (ip). After 45 min, a morphine withdrawal syndrome was precipitated by naloxone (2 mg/kg, ip), and morphine withdrawal signs were observed and evaluated for 15 min. Harmine (5 and 10 mg/kg) attenuated significantly the intensity of all signs of morphine withdrawal except for jumping. While jumping behaviour appearing in morphine withdrawal was intensified by harman (5 and 10 mg/kg) treatment, harmine administration did not produce any significant change in the intensity of this sign. Harman attenuated significantly the intensity of wet dog shakes, writhing, defecation, tremor and ptosis. However, it produced no significant changes in the intensity of teeth chattering and diarrhea. Our results suggest that harman and harmine, beta-carbolines, have some beneficial effects on naloxone-precipitated morphine withdrawal syndrome in rats. Findings from the present study also indicated that harmine was more effective than harman on morphine abstinence syndrome.
Keywords: Animals; Male; Rats; Rats, Wistar; Carbolines; Injections, Intraperitoneal; Behavior, Animal; Hallucinogens; Harmine; Morphine Dependence; Naloxone; Substance Withdrawal Syndrome